Histological Features of Celiac-Disease-like Conditions Related to Immune Checkpoint Inhibitors Therapy: A Signal to Keep in Mind for Pathologists - Rachele Del Sordo; Umberto Volta; Vassilios Lougaris; Paola Parente; Angelo Sidoni; Mattia Facchetti; Gabrio Bassotti; Illuminato Carosi; Celeste Clemente; Vincenzo Villanacci (Diagnostics, 2022)
Immune checkpoint inhibitors (ICIs) targeting cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), programmed cell death protein (PD-1), and its ligand PDL-1, are finding increasing application in the treatment of malignant neoplasms. The widespread clinical use of these drugs, however, resulted in the discovery of side effects. The occurrence of celiac disease (CD) after ICIs therapy has been reported in the literature, but its incidence remains unknown and the role of ICIs in its onset is not yet clear. In this review, we examine the published data on this topic in order to better understand and define this entity from a histological point of view. We performed an electronic literature search to identify original reports in which CD or pathological CD-like conditions were documented histologically in patients treated with ICIs. We identified ten papers. A total of twenty-five patients were included in these publications, eleven of them receiving a serologic and histological diagnosis of CD, and four a histological diagnosis of CD-like conditions, in which pathogenesis appears to be multifactorial. ICIs can cause a CD-like enteropathy and biopsies with clinical integration are crucial to diagnose this condition. CD rarely has been observed during treatment with ICIs and its morphological aspects are similar to ICIs-CD enteropathy. Moreover, the onset of ICIs-CD may have a distinct immune mechanism compared to classical CD. Thus, the pathologists must make a histological diagnosis of CD with caution and only in adequate clinical and serological context.